(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The use of nucleopolyhedroviruses (NPVs) can provide an effective and environmentally benign alternative to synthetic chemicals. The efficacy and persistence of their occlusion bodies may be affected by several factors. The present study investigated the efficacy of isolate Chin-IA (I-A) (ChinSNPV) on third-instar Chrysodeixis includens larvae after 10 days of its application in soybean plants under semi-field conditions. Two concentrations of virus (2x1011 and 10x1011 PIB ha-1) and water (control treatment) were applied in soybean plants. Leaves were collected 0, 2, 4, 6, 8 and 10 days after application of treatments, and then used as disc format to feed the soybean looper larvae in the lab. It was considered a split plot scheme with a randomized complete block design (three treatments and eight repetitions) and the mortality data adjusted to a regression equation using the exponential decay model. In the day of application, the lowest and highest virus concentration caused 87.5 and 100% of mortality of larvae, respectively. However, their efficiency was reduced, on average, 70% after four days of the application. Among the factors may have compromised the persistence and activity of the isolate studied, the time after its application and ultraviolet radiation may have had a strong influence on this results. Its notable the potential use of ChinSNPV in programs for the management of this pest in soybean. Similarly, the properly application of this virus at sundown will ensure its efficiency for an extended period.